Effects of Copper on Euglena sp. Local Strains and Remediation Capabilities - Ardipeni, Witia; Suyono, Eko Agus; Dewayanto, Nugroho; Mufida, Na’imatul; Erfianti, Tia; Amelia, Ria; Kurnianto, Dedy (HAYATI Journal of Biosciences, 2025)
One of the well-known industries in Yogyakarta is the Kotagede silver craft, which produces heavy metal waste, one of which is copper. The copper content in the liquid waste of electroplating Kotagede silver crafts is 4.628 mg/L. At the same time, Indonesian Government Regulation No. 22 (2021) stipulates a critical limit of Copper (Cu) content in river and lake water, which is 0.2 mg/L. The purpose of the study was to analyze the effects of copper on local strains of Euglena sp. (growth, photosynthetic pigment production, and superoxide dismutase enzyme) as well as the effectiveness of Euglena sp. in copper remediation. The study was conducted by adding a copper solution obtained from CuSO4•5H2O to the culture medium of Euglena sp. The parameters observed in the study were growth (number of cells and biomass), photosynthetic pigment content (chlorophyll a, chlorophyll b, carotenoid total), Superoxide dismutase enzyme of Euglena sp. as well as the effectiveness of Euglena sp. in copper remediation. The results showed that copper inhibited the growth of Euglena sp. The highest growth was the control treatment (without adding copper to the culture medium). Likewise, the content of photosynthetic pigments and the culture of Euglena sp. exposed to copper were lower when compared to the control culture. The activity of the SOD enzyme is increased in cultures exposed to copper. The result of the research is Cu metal absorption efficiency by Euglena sp. by 21.93%, 10.93%, and 9.47% for a Cu concentration of 10 ppm, 15 ppm, and 20 ppm.